Deregulating the Evacuated Body:: Rohinton Mistry’s “Squatter” - Eustace, John (Studies in Canadian Literature / Études en littérature canadienne)

(untitled) (The University of New Brunswick, 2003)
Images of squalor, and more particularly evacuated bodies, are pervasive in Rohinton Mistry's fiction, most notably the short story "Squatter" in Tales from Firozsha Baag. However, such images do not debase Mistry's characters in a racialized discourse but elevate them, acknowledging their basic humanity to challenge such discourses that would overdetermine and further disenfranchise them. If Mistry's fiction is full of shit, that shit is fertilizer, nurturing a fundamental respect for humanity and its persistence even in the most dire of circumstances.